Investigation of the Effects of 8-Week Selected Pliometric Training Program on Vertical Jump and Agility in Female Volleyball Players - Halil Çolak, Ömer Güzel (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The aim of this study was to investigate the effects of pliometric training on vertical jump and agility in young female volleyball players. Methods: Normal training was applied to the groups and pliometric study protocol was applied to the training program of the training group for 8 weeks. Pre-test and post-test were applied before and after the program. SPSS 25.0 program was used in the analyzes. Descriptive statistics were expressed as frequency (n), average (Mean), standard deviation (SS), minimum (Min) and maximum (Max) values. Independent samples t test was used for comparison of two groups and paired sample t test was used for intragroup comparisons. Statistical significance was evaluated at p <0.05. Results: In the analyzes, A total of 50 female athletes, 25 of whom were in experimental and 25 of which were in the control group, participated in the study. The mean age of the training group was 14,56 ± 1,45 years, body weight was 55,79 ± 7,93 kg and height was 165,6 ± 7,26 cm. The mean age of the control group was 14,88 ± 1,86 years, body weight was 54,4 ± 9,82 kg and height was 164,56 ± 6,59 cm. Pliometric training applications have significant contributions to BF percentage, anaerobic capacity, (p<0,05), vertical jump, leg strength, long jump, hegzagonal test, 505 agility test, Illinois agility test, and back strength (p<0,001) level of significance. Conclusions: It was concluded that it will contribute to strength development by decreasing the intensity in sports branches and middle school Physical Education classes which require strength and agility, especially in volleyball and in many branches in training programs and through game training and pliometric exercises.